Canine transmissible venereal tumor. The oldest clonal lineage known in nature - Zarlenga Regiani , Marta; VASCONCELLOS, MARCEL (Pubvet, 2018)
The gene sequencing technique, used in the study of the clonal origin of canine venereal transmissible tumor (CTVT), opened up new possibilities of probing genetic vulnerabilities of cancer, and host-tumor relations. Analogous to Darwinian evolution, tumor cells with higher adaptive potential present a selective advantage over less apt cells, and thus, naturally occurring transmissible cancer, represents an ideal model for the evolutionary investigation between cancer cells in their Microenvironment, and the surrounding macroenvironment. In order to discuss the impact of the recent findings in this field, an analysis of publications indexed in the PubMed® database (National Institutes of Health) using the English descriptors: venereal canine transmissible Tumor, transmissible venereal canine, transmissible canine. Genomic studies have shown that the clonal lineage of the CTVT is the oldest known tumor line (about 11,000 years old), and can be transmitted by allogeneic transfer. Unique aspects such as evasion to the host immune system were also reviewed.
Keywords: cancer; dogs; epidemiology